GLOBALISATION AND THE EROSION OF TRADITION: MODELLING THE IMPACT OF GLOBAL CULTURE ON LOCAL CUSTOMS - Loso Judijanto; Aslan Aslan (CV. Adiba Aisha Amira, 2024)
This study analyses the impact of globalisation on local customs, highlighting how the process of globalisation can lead to the erosion of traditions as well as affect long-entrenched cultural values. Technology and mass media act as key agents in accelerating people's exposure to foreign cultures, often displacing traditional practices. However, globalisation also brings opportunities for revitalisation and innovation in local traditions, allowing for hybrid cultures that enrich people's lives. To manage such impacts, a holistic approach is needed that involves co-operation between the government, cultural institutions and communities in preserving and adapting local cultural values with modern technology and innovation. This approach is expected to achieve a balance between harnessing the benefits of globalisation and maintaining traditional cultural identity.